Intuitionistic Fuzzy Time Series: An Approach for Handling Nondeterminism in Time Series Forecasting - Kumar, Sanjay; Gangwar, Sukhdev Singh (IEEE transactions on fuzzy systems, 2016)
Atanassov introduced the notion of intuitionistic fuzzy set as generalization of the fuzzy set, which has been proved to be very useful tool in handling nondeterminacy (hesitation) in the system. In the implementation of fuzzy time series forecasting, nondeterminacy is always neglected without any reason. In this paper, we give the notion of intuitionistic fuzzy time series to handle the nondeterminism in time series forecasting. An intuitionistic fuzzy time series forecasting model is also proposed. The proposed intuitionistic fuzzy time series forecasting method uses intuitionistic fuzzy logical relations on time series data. Performance of the proposed method is verified by applying it on two time series data. The effectiveness of the proposed intuitionistic fuzzy time series forecasting method is verified by comparing the forecasted output with other intuitionistic-fuzzy-set-based fuzzy time series forecasting methods using root-mean-square error and average forecasting error.